Experimental investigation on heat transfer enhancement by using porous twisted plate as an insert in a fitted tube - Roslim, M.K. (Asian Research Publishing Network, 2015)
This article reports the investigation on the effects of porous twisted plate as insert to enhance heat transfer performance and flow characteristic fora single fitted tube. The porous twisted plate was designed with 3 different numbers of holes (1Hole, 2Holes and 3Holes) with 4mm diameter on each segment. The actual fitted tube of the boiler was used and inserted with plain and porous twisted plates. The collecting result was compared with the plain tube without any insert. The result shows that creation of holes changed the flow profile and generating secondary flow and approaching turbulence flow. Furthermore, the velocity of the flow was increased and allowing more fluid mixing inside the tube thus provide more heat transfer across the tube. Porous twisted plate with larger numbers of holes enhance better heat transfer rate compared to plain tube and plain twisted plate. Â© 2006-2015 Asian Research Publishing Network (ARPN).